Antimicrobial Activity of Lactic Acid Bacteria Isolated from Traditional Fermented Food (Tribhuvan University Journal of Microbiology, 2021)
Objective: The main objective is to isolate Lactic acid bacteria from traditional fermented food of Kathmandu valley and to study their antimicrobial properties by agar well diffusion method.Methods: A total of 30 samples of 4 different types of traditional fermented food (Gundruk and sinki, Pickles and Dahi) were obtained from Kathmandu valley and processed in Microbiology Laboratory of Padma Kanya Multiple Campus. For identification of Lactic acid bacteria (LAB), Gram staining, catalase and motile tests were done. In the carbohydrate fermentation test, all isolates were processed for fermentation of glucose, lactose, sucrose and fructose. Bacteriocin was extracted by precipitation method. Antibiotic susceptibility of the isolates was determined by using modified Kirby-Bauer disc diffusion method. The antimicrobial activity of Lactic acid bacterial (LAB) was done by agar well diffusion method.Results: A total of 21 LAB isolates were identified which were 10 Lactobacillus spp (47.6%), 8 Pediococcus spp (38.0%) and 3 Streptococcus spp (14.3%). The antimicrobial activity of bacteriocin showed inhibitory activity against Shigella spp, Escherichia coli and Bacillus spp but did not show inhibition to Staphylococcus aureus, Salmonella spp. and Klebsiella pneumoniae. For the quality control, the antimicrobial activity of bacteriocin was done on ATCC (25923) Staphylococcus aureus. All isolates were susceptible to ampicillin while resistant to nalidixic acid and Co-trimoxazole.Conclusion: The present study showed the bacteriocin produced by LAB from traditional fermented food (Gundruk and Sinki, yogurt and Pickle) showed antimicrobial activity against different bacteria which underline its important role in improving food quality and increasing safety.